Measuring Economic Competence of Secondary School Students in Germany - Tim Kaiser; Luis Oberrauch; Günther Seeber (ZBW – Leibniz Information Centre for Economics, 2019)
We introduce a test of economic competence for German-speaking secondary school students and provide evidence from a large-scale assessment with 6,230 students from grades seven to ten. The article presents the development and psychometric properties of the scale, as well as an investigation of predictors of economic competence. We find evidence of a gender gap favoring male students, lower scores for students with a migration background, and parents' socioeconomic background being a predictor of test performance. Additionally, we document sizeable differences between tracks, as well as gains in economic competence across grades in the order of magnitude of 0.06 to 0.2 standard deviations per year. The article concludes with perspectives on an impact evaluation of a curriculum reform introducing mandatory economic education in secondary school.
https://dx.doi.org/10.17605/OSF.IO/EMWYJ
Keywords: A21; 330; economic competence; economic literacy; item response theory; school economics